Carbon fiber sizing agent, preparation method of carbon fiber sizing agent, sized carbon fiber and preparation method of sized carbon fiber
By using benzoxazine resin and amino-modified resin in the carbon fiber sizing agent for high-temperature cross-linking reaction, a complex polymer network is formed, which solves the problem of insufficient heat resistance of the existing sizing agent, and significantly improves the interface binding force between the carbon fiber and the resin matrix and the overall performance of the composite material.
Patent Information
- Application Number
- CN202411847697.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing emulsion type carbon fiber sizing agent has poor heat resistance, resulting in weak interface bonding strength of composite materials formed by carbon fiber and resin matrix.
Using a sizing agent containing benzoxazine resin and an amino-modified resin, a complex polymer network is formed by grafting cross-linking and self-crosslinking reaction between the benzoxazine resin and the amino-modified resin at high temperature to improve the heat resistance and interface binding force of the resin.
The heat resistance and interface performance of the sizing agent are significantly improved, the bonding force between carbon fiber and resin matrix is enhanced, the risks of interface peeling and layering are reduced, and the overall performance of the composite material is improved.
Smart Images

Figure BDA0005189687670000111 
Figure BDA0005189687670000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of carbon fiber sizing agents, and in particular to a carbon fiber sizing agent and a preparation method thereof, sized carbon fiber and a preparation method thereof. Background Art
[0002] After low-temperature and high-temperature carbonization treatment, the surface of carbon fiber is inert, with few groups interacting with the resin matrix, weak interface bonding ability, and fluffy and disordered state without tension. The surface of carbon fiber needs further sizing treatment. Through the sizing process, the bundle protection of carbon fiber is achieved, and the breakage of single fiber caused by friction is reduced; at the same time, the sizing agent acts as the interface layer connecting the carbon fiber and the matrix resin, and the polar groups on the surface of carbon fiber are increased, which improves the wettability and permeability of the carbon fiber surface and the matrix resin, and plays a role in enhancing the interface bonding strength between the resin and the fiber.
[0003] At present, emulsion sizing is mostly used at home and abroad. Emulsion sizing is mainly based on resin and prepared into a water-based emulsion with a certain emulsifier. The concentration of the water emulsion is easy to control and has excellent safety. However, most of the existing emulsion sizing agents have poor heat resistance, resulting in weak interface bonding strength of the composite material formed by the carbon fiber treated with the sizing agent and the resin matrix. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing a carbon fiber sizing agent and a preparation method thereof, sized carbon fiber and a preparation method thereof, so as to improve the heat resistance and interface properties of the sizing agent.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, an embodiment of the present application provides a carbon fiber sizing agent, comprising a benzoxazine resin, an amino-modified resin, an emulsifier, and a solvent.
[0007] This application uses benzoxazine resin as the main raw material, and then introduces amino modified resin, so that when the sizing agent is sizing the carbon fiber, the benzoxazine resin can undergo graft crosslinking reaction with the amino modified resin at high temperature, and the benzoxazine resin itself will undergo epoxy ring-opening polymerization to form a self-crosslinking reaction. Among them, the network structure formed by self-crosslinking can effectively improve the heat resistance of the resin, because this structure can disperse heat energy and reduce heat conduction, so that the resin is not easy to degrade under high temperature environment, and the formation of this cross-linked network increases the rigidity and toughness of the resin, so that the sizing agent maintains good mechanical properties at high temperature, thereby improving the strength of the composite material formed by the combination of carbon fiber and resin matrix. The graft crosslinking reaction forms a new chemical bond between the benzoxazine resin and the amino resin, and enhances the bonding force between the carbon fiber and the resin matrix. This enhanced interface bonding force can effectively reduce the risk of interface peeling and delamination, and improve the overall performance of the composite material; moreover, the chemical bonds generated by the graft crosslinking reaction can remain stable at high temperature, further improving the heat resistance of the material, and this strong interface characteristic enables the composite material to still maintain good mechanical properties and stability under high temperature environment.
[0008] In some embodiments of the present application, the composition includes, by weight: 100 parts of benzoxazine resin, 20-50 parts of amino-modified resin, 20-40 parts of solvent and 30-50 parts of emulsifier.
[0009] In the sizing agent, benzoxazine resin as the main component provides excellent heat resistance and thermal stability, so that the sizing agent can still maintain its physical and chemical properties in a high temperature environment. It can undergo self-crosslinking reaction at high temperature to form a three-dimensional crosslinked network, which significantly enhances the mechanical strength and rigidity of the material, thereby improving the overall performance of the composite material. By adding amino-modified resin, it can not only undergo graft crosslinking reaction with benzoxazine resin to form a more complex polymer network, but also effectively enhance the interfacial bonding force between carbon fiber and resin matrix, reduce the risk of delamination and peeling, and improve interfacial performance. Furthermore, the introduction of solvent plays an important role in regulating the viscosity of the sizing agent, making it easier to apply and ensure uniformity, thereby improving the sizing effect. At the same time, the solvent also promotes the emulsification process of the sizing agent, so that the effective ingredients can be evenly dispersed, further enhancing the stability of the sizing agent. The use of emulsifier plays a key role in stabilizing the emulsion, preventing delamination and precipitation, and improving the consistency and reliability of the sizing agent during storage and use.
[0010] In some embodiments of the present application, the particle size of the carbon fiber sizing agent is 200-500 nm.
[0011] The particle size of the carbon fiber sizing agent is within the particle size range of 200-500nm, which can effectively improve the dispersibility, enhance the interface bonding force, increase the reaction activity, improve the fluidity, and has good adaptability.
[0012] In some embodiments of the present application, the benzoxazine resin includes one or more of bisphenol A-type benzoxazine, bisphenol F-type benzoxazine and phenol-type benzoxazine.
[0013] These types of benzoxazine resins not only offer excellent thermal stability and mechanical properties, but also possess good chemical resistance and tunability.
[0014] In some embodiments of the present application, the amino-modified resin includes one or more of urea-formaldehyde resin, melamine-formaldehyde resin and benzoguanamine-formaldehyde resin.
[0015] These amino-modified resins have good adhesive properties and can enhance the bonding between carbon fibers and the resin matrix. They also have good thermal stability at high temperatures and can undergo graft cross-linking reactions with other resins (such as benzoxazine resins) at high temperatures to form a stable cross-linked network. This cross-linking reaction not only improves the heat resistance of the material, but also enhances its mechanical properties and toughness.
[0016] In some embodiments of the present application, the solvent includes one or more of toluene, acetone and tetrahydrofuran.
[0017] The selection of solvents such as toluene, acetone and tetrahydrofuran provides good solvency, appropriate volatility and fluidity, while being able to effectively adjust the viscosity and improve the overall performance of the sizing agent.
[0018] In some embodiments of the present application, the emulsifier includes one or more of alkylphenol polyoxyethylene ether, polyethylene glycol and polyoxyethylene sorbitan fatty acid ester.
[0019] These emulsifiers provide excellent emulsifying properties, and can also improve the stability of the sizing agent emulsion, as well as improve the dispersibility of the components in the sizing agent so that the active ingredients can be evenly distributed.
[0020] In a second aspect, an embodiment of the present application provides a method for preparing the above-mentioned carbon fiber sizing agent, comprising: stirring and mixing benzoxazine resin, amino-modified resin, emulsifier and solvent, adding water for emulsification and phase transfer, and obtaining a carbon fiber sizing agent.
[0021] The method comprises stirring and mixing benzoxazine resin, amino-modified resin, emulsifier and solvent, and then adding water for emulsification and phase inversion. The process steps are relatively simple and easy to operate. This simplified process helps to improve production efficiency and reduce production time and cost.
[0022] In a third aspect, an embodiment of the present application provides a sized carbon fiber, comprising a carbon fiber and a sizing agent coating attached to the surface of the carbon fiber, wherein the sizing agent coating is formed by any of the above-mentioned carbon fiber sizing agents.
[0023] In the sized carbon fiber, the sizing agent coating can effectively enhance the bonding force between the carbon fiber and the resin matrix, and the sizing agent used (containing benzoxazine resin and amino-modified resin) has excellent heat resistance, so that the sized carbon fiber can maintain good performance in a high temperature environment.
[0024] In some embodiments of the present application, the mass fraction of the sizing agent coating on the carbon fiber is 0.5-1.0%.
[0025] Controlling the sizing amount (mass fraction of sizing agent coating to carbon fiber) to 0.5-1.0% can more easily achieve a uniform coating effect, and can effectively enhance the interface bonding strength and heat resistance, as well as maintain the excellent mechanical properties of carbon fiber.
[0026] In a fourth aspect, an embodiment of the present application provides a method for preparing the above-mentioned sized carbon fiber, comprising: preparing a sizing agent into a sizing agent solution, immersing the carbon fiber in the sizing agent solution, and then drying and heat-curing the treated carbon fiber in sequence to obtain sized carbon fiber.
[0027] The method adopts the method of preparing the sizing agent into a solution and then soaking it, which is simple to operate and easy to implement. Among them, by immersing the carbon fiber in the sizing agent solution, the uniformity of the coating can be improved, and the soaking process can make the sizing agent fully penetrate into each strand of the carbon fiber, thereby improving the functionalization degree of the surface and enhancing the interface bonding force; during the drying and heating curing process, the components in the sizing agent can be effectively cross-linked to form a stable coating. This cross-linking process not only improves the mechanical strength and heat resistance of the coating, but also enhances the bonding force between the carbon fiber and the resin matrix, and improves the overall performance of the composite material.
[0028] In some embodiments of the present application, the drying conditions include: a drying temperature of 130-160° C. and a drying time of 30-60 seconds.
[0029] The drying conditions are set at a temperature of 130-160°C and a time of 30-60s, which can effectively remove the solvent, prevent carbon fiber damage, promote cross-linking reaction, enhance coating adhesion, optimize the subsequent curing process, and improve production efficiency.
[0030] In some embodiments of the present application, the conditions for heating and curing include: a heating temperature of 180-220° C. and a heating time of 30-60 s.
[0031] The heating curing conditions are set at 180-220°C and 30-60s, which can effectively promote cross-linking, improve coating uniformity, improve heat resistance and chemical stability, enhance adhesion, optimize processing performance, and improve production efficiency. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] The following is a detailed description of a carbon fiber sizing agent and a preparation method thereof, a sized carbon fiber and a preparation method thereof according to an embodiment of the present application.
[0034] An embodiment of the present application provides a carbon fiber sizing agent, including a benzoxazine resin, an amino-modified resin, an emulsifier, and a solvent.
[0035] Benzoxazine is a class of substances containing heterocyclic structures synthesized from phenolic, aldehyde and primary amine compounds. The present application uses benzoxazine resin as the main component and then introduces an amino-modified resin, so that when the sizing agent is used to size carbon fibers, the benzoxazine resin can undergo a series of cross-linking reactions with the amino-modified resin at high temperatures, including self-cross-linking reactions and graft cross-linking reactions. After sizing the carbon fibers, they are dried. At high temperatures, on the one hand, the benzoxazine resin itself undergoes epoxy ring-opening polymerization to form a self-cross-linking reaction. Among them, this process allows chemical bonds to be formed between the molecular chains of the benzoxazine resin, forming a three-dimensional network structure. The network structure can effectively improve the heat resistance of the resin, increase the rigidity and toughness of the resin, and enable the sizing agent to maintain good mechanical properties at high temperatures, thereby improving the strength of the composite material formed by the combination of carbon fiber and substrate; on the other hand, the O six-membered oxazine ring in the benzoxazine resin undergoes a grafting and cross-linking reaction with the amino group in the amino resin. This grafting and cross-linking reaction not only improves the thermal stability of the sizing agent, but also significantly enhances the bonding force between the carbon fiber and the resin matrix; through the grafting and cross-linking reaction, a more complex polymer network is formed, which further improves the interface performance and reduces the risk of delamination and debonding.
[0036] The composition comprises, by weight: 100 parts of benzoxazine resin, 20-50 parts of amino-modified resin, 20-40 parts of solvent and 30-50 parts of emulsifier.
[0037] In the sizing agent, benzoxazine resin as the main component provides excellent thermal stability and high temperature resistance, which enables the sizing agent to maintain its physical and chemical properties under high temperature environment. Benzoxazine resin can spontaneously undergo epoxy ring-opening polymerization at high temperature to form a cross-linked network, which enhances the mechanical strength and rigidity of the resin and improves the overall performance of the composite material. Amino-modified resin can undergo graft cross-linking reaction with benzoxazine resin to form a more complex polymer network, which not only improves heat resistance but also improves the toughness of the material. Amino-modified resin can enhance the bonding force between carbon fiber and resin matrix, improve interface performance, and reduce the risk of delamination and peeling. The solvent can adjust the viscosity of the sizing agent, so that the sizing agent can be evenly coated on the surface of carbon fiber, thereby improving the sizing effect; and the solvent helps the emulsification process of the sizing agent, so that the effective ingredients can be evenly dispersed in the emulsion, thereby improving the stability of the sizing agent. The emulsifier plays a role in stabilizing the emulsion in the formula, preventing delamination and precipitation, and can also improve the dispersibility of each component in the sizing agent, so that the effective ingredients can fully contact the carbon fiber, thereby improving the sizing effect.
[0038] In the embodiment of the present application, the particle size of the carbon fiber sizing agent is 200-500nm.
[0039] The sizing agent with a particle size of 200-500nm can maintain good dispersibility and fluidity in water or organic solvents, so that the sizing agent can be evenly coated on the surface of carbon fiber and reduce the generation of bubbles and defects. Moreover, the sizing agent in this particle size range can better penetrate into the microstructure of carbon fiber, thereby increasing the contact area between carbon fiber and resin matrix. Then improve the interfacial bonding force, reduce the risk of delamination and peeling, and enhance the overall performance of the composite material. In addition, the sizing agent in this particle size range has a large specific surface area, which can make the reaction activity between carbon fiber and resin matrix higher, and then promote the occurrence of cross-linking reaction, further enhancing the heat resistance and mechanical properties of the material.
[0040] As an example, the benzoxazine resin includes, but is not limited to, one or more of bisphenol A-type benzoxazine, bisphenol F-type benzoxazine, and phenol-type benzoxazine.
[0041] Among them, bisphenol A, bisphenol F and phenol benzoxazine resins all have high thermal stability, good tolerance to a variety of chemicals (such as acids, alkalis and solvents), and good mechanical strength and toughness. Among them, bisphenol A resin has excellent tensile strength and impact resistance, while bisphenol F resin is outstanding in wear resistance. These benzoxazine resins can undergo self-crosslinking or crosslinking reactions with other components at high temperatures to form a complex polymer network. This crosslinking ability not only improves the heat resistance and mechanical properties of the material, but also improves the interfacial bonding between carbon fiber and resin matrix.
[0042] As an example, the amino-modified resin includes, but is not limited to, one or more of urea-formaldehyde resin, melamine-formaldehyde resin, and benzoguanamine-formaldehyde resin.
[0043] Among them, urea-formaldehyde resin and melamine formaldehyde resin have good bonding properties and can effectively enhance the bonding force between carbon fiber and resin matrix. This strong bonding performance helps to improve the overall structural strength of the composite material and reduce the risk of peeling and delamination. Melamine formaldehyde resin and benzoguanamine formaldehyde resin have good thermal stability at high temperatures and can maintain their physical and chemical properties in high temperature environments. These amino-modified resins have good tolerance to a variety of chemicals (such as acids, alkalis and solvents), allowing the composite materials to maintain excellent performance in harsh environments. Moreover, these amino-modified resins can undergo cross-linking reactions with other resins (such as benzoxazine resins) at high temperatures to form a stable cross-linked network. This cross-linking reaction not only improves the heat resistance of the material, but also enhances its mechanical properties and toughness.
[0044] By way of example, the solvent includes, but is not limited to, one or more of toluene, acetone, and tetrahydrofuran.
[0045] Toluene, acetone and tetrahydrofuran are excellent solvents that can effectively dissolve benzoxazine resins and amino-modified resins. This good solubility allows the active ingredients of the sizing agent to be evenly dispersed, improving the performance of the sizing agent. These solvents have moderate volatility and can evaporate quickly during the coating and curing process, reducing the drying time of the material. This rapid volatility helps improve production efficiency and allows the sizing agent to cure quickly to form a stable coating. Toluene, acetone and tetrahydrofuran can improve the fluidity of the sizing agent, making it easier to flow and distribute during the application process, reducing the generation of bubbles and defects, thereby improving the quality of the final product.
[0046] As an example, the emulsifier includes, but is not limited to, one or more of alkylphenol polyoxyethylene ether, polyethylene glycol, and polyoxyethylene sorbitan fatty acid ester.
[0047] These emulsifiers have excellent emulsifying ability and can effectively disperse benzoxazine resin and amino modified resin in water phase or organic solvent to form a stable emulsion, which improves the uniformity of the sizing agent and helps to improve the coating effect. Among them, alkylphenol polyoxyethylene ether and polyethylene glycol can significantly improve the stability of the emulsion and prevent stratification and precipitation. The above emulsifiers can improve the dispersibility of each component in the sizing agent so that the effective ingredients can be evenly distributed; they can also improve the interfacial compatibility between the resin and the carbon fiber and enhance its bonding strength; by forming a good interfacial contact, the overall performance of the composite material can be improved and the risk of stratification and peeling can be reduced.
[0048] The preparation method of the above-mentioned carbon fiber sizing agent is described below.
[0049] A method for preparing the above-mentioned carbon fiber sizing agent comprises: stirring and mixing benzoxazine resin, amino modified resin, emulsifier and solvent, adding water for emulsification and phase inversion, and obtaining the carbon fiber sizing agent.
[0050] In this preparation method, the organic phase can be effectively converted into a stable emulsion by stirring and mixing, so that the effective components of the resin can be well dispersed in the aqueous phase, thereby improving the uniformity and stability of the sizing agent. By using the aqueous phase for emulsification, the dependence on organic solvents is reduced, and the emulsification process can significantly improve the stability of the sizing agent and prevent stratification and precipitation. In general, the preparation method achieves uniform mixing of the components, effective emulsification, and improved stability by simplifying the process flow.
[0051] An embodiment of the present application also provides a sized carbon fiber, including a carbon fiber and a sizing agent coating attached to the surface of the carbon fiber, wherein the sizing agent coating is formed by any of the above-mentioned carbon fiber sizing agents.
[0052] By coating the sizing agent of the present application, the surface of the carbon fiber is functionalized, thereby improving its compatibility with the resin, thereby reducing the risk of delamination and peeling, and improving the overall strength of the composite material; the sizing agent has excellent heat resistance, so that the sized carbon fiber can maintain good performance in a high temperature environment.
[0053] Wherein, the mass fraction of the sizing agent coating to the carbon fiber is 0.5-1.0%. As an example, the mass fraction of the sizing agent coating to the carbon fiber includes but is not limited to 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%.
[0054] Within this sizing amount range, the coating can be made more uniform, and the thickness of the sizing agent coating formed is moderate, while enhancing the interface bonding strength and heat resistance, it can also maintain the excellent mechanical properties of carbon fiber.
[0055] The preparation method of the above-mentioned sizing carbon fiber is described below.
[0056] A method for preparing the above-mentioned sized carbon fiber comprises: preparing a sizing agent into a sizing agent solution, immersing the carbon fiber in the sizing agent solution, and then sequentially drying and heating and curing the treated carbon fiber to obtain the sized carbon fiber.
[0057] The drying conditions include: drying temperature of 130-160° C. and drying time of 30-60 seconds.
[0058] In this temperature range, the solvent in the sizing agent solution can be removed quickly and effectively, improving the uniformity and stability of the coating. In the above drying temperature range, the partial cross-linking reaction of the resin component in the sizing agent can be promoted, which helps to improve the mechanical strength and heat resistance of the coating.
[0059] The conditions for heating and curing include: heating temperature of 180-220° C. and heating time of 30-60 seconds.
[0060] In the temperature range of 180-220℃, the cross-linking reaction of the resin in the sizing agent can be effectively promoted. This process helps to form a stable three-dimensional network structure, significantly improving the mechanical strength and heat resistance of the coating, thereby enhancing the overall performance of the composite material. The heating time of 30-60s can make the coating evenly heated during the curing process. Through heating curing, the heat resistance and chemical stability of the coating can be significantly improved, as well as the adhesion between the sizing agent coating and the carbon fiber.
[0061] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0062] Example 1
[0063] This embodiment provides a carbon fiber sizing agent, and the preparation method thereof comprises the following steps:
[0064] 100 g of bisphenol A type benzoxazine resin, 20 g of urea-formaldehyde resin, 30 g of alkylphenol polyoxyethylene ether and 20 g of acetone were stirred and mixed, and water was added for emulsification and phase inversion to obtain a carbon fiber sizing agent.
[0065] Example 2
[0066] This embodiment provides a carbon fiber sizing agent, and the preparation method thereof comprises the following steps:
[0067] 100 g of bisphenol F type benzoxazine resin, 35 g of melamine formaldehyde resin, 40 g of polyethylene glycol and 30 g of toluene were stirred and mixed, and water was added for emulsification and phase inversion to obtain a carbon fiber sizing agent.
[0068] Example 3
[0069] This embodiment provides a carbon fiber sizing agent, and the preparation method thereof comprises the following steps:
[0070] 100 g of phenol-type benzoxazine resin, 40 g of melamine formaldehyde resin, 50 g of polyoxyethylene sorbitan fatty acid ester and 40 g of tetrahydrofuran were stirred and mixed, and water was added for emulsification and phase inversion to obtain a carbon fiber sizing agent.
[0071] Example 4
[0072] This embodiment provides a carbon fiber sizing agent, and the preparation method thereof comprises the following steps:
[0073] 100 g of bisphenol A type benzoxazine resin, 20 g of urea-formaldehyde resin, 20 g of alkylphenol polyoxyethylene ether and 10 g of acetone were stirred and mixed, and water was added for emulsification and phase inversion to obtain a carbon fiber sizing agent.
[0074] Example 5
[0075] This embodiment provides a carbon fiber sizing agent, and the preparation method thereof comprises the following steps:
[0076] 100 g of bisphenol A type benzoxazine resin, 60 g of urea-formaldehyde resin, 30 g of alkylphenol polyoxyethylene ether and 20 g of acetone were stirred and mixed, and water was added for emulsification and phase inversion to obtain a carbon fiber sizing agent.
[0077] Example 6
[0078] This embodiment provides a carbon fiber sizing agent, and the preparation method thereof comprises the following steps:
[0079] 100 g of bisphenol A type benzoxazine resin, 15 g of urea-formaldehyde resin, 30 g of alkylphenol polyoxyethylene ether and 20 g of acetone were stirred and mixed, and water was added for emulsification and phase inversion to obtain a carbon fiber sizing agent.
[0080] Comparative Example 1
[0081] This comparative example is substantially the same as Example 1, except that no urea-formaldehyde resin is added.
[0082] Comparative Example 2
[0083] This comparative example is substantially the same as Example 1, except that no bisphenol A type benzoxazine resin is added.
[0084] Some parameters of the above-mentioned Examples 1-6 and Comparative Examples 1 and 2 are detailed in Table 1.
[0085] Table 1
[0086]
[0087] Test Example 1
[0088] The sizing agents prepared in the above-mentioned Examples 1-6 and Comparative Examples 1 and 2 are respectively prepared into sizing agent solutions, and the same carbon fibers are divided into 7 groups, which are immersed in the above-mentioned sizing agent solutions respectively, and then the treated carbon fibers are first dried at 140°C for 50s, and then heated and cured at 210°C for 50s to obtain sized carbon fibers (sizing amount is 0.5-1.0%), epoxy resin E51 is mixed with curing agent DDS to form an epoxy resin matrix mixture, and the above-mentioned groups of sized carbon fibers are impregnated with the epoxy resin matrix mixture, and cured and formed to obtain carbon fiber composite materials. This test example measures the thermal decomposition starting temperature of these sizing agents and the interlaminar shear strength of the composite materials.
[0089] The determination of the thermal decomposition starting temperature is: the temperature at which the thermal decomposition mass volatilization of the effective solid components of the sizing agent reaches 5% in an air environment.
[0090] Determination of interlaminar shear strength: Tested in accordance with national standard GB / T30969-2014.
[0091] Please see Table 2 for the measurement results of the above items.
[0092] Table 2
[0093]
[0094] As can be seen from Table 2, after the solvent and emulsifier content in Example 4 is reduced, the particle size of the sizing agent increases significantly, resulting in poor uniformity of the sizing agent on the carbon fiber, which in turn causes a decrease in the interlaminar shear strength of the carbon fiber composite material, thereby reducing the interface bonding ability of the sizing agent. By comparing Examples 1, 5 and 6, it can be found that the mass ratio of the amino-modified resin to the benzoxazine resin is in the range of (2-5):1, which is more conducive to improving the heat resistance and interface bonding ability of the sizing agent.
[0095] In Example 4, due to the low emulsifier content, the emulsification effect is reduced. Secondly, due to the low solvent content, the resin is not fully mixed and dissolved, and the difficulty of resin emulsification increases, which in turn causes the particle size of the sizing agent emulsion to increase.
[0096] In Comparative Example 1, no amino-modified resin was added, and it was found that the thermal decomposition temperature decreased significantly, indicating that the heat resistance of the sizing agent was reduced. At the same time, the interlaminar shear strength of the carbon fiber composite material also decreased, and the interface bonding reaction ability became weaker.
[0097] In Comparative Example 2, bisphenol A benzoxazine resin was not added, and it was found that both the thermal decomposition temperature and the interlaminar shear strength decreased significantly, indicating that the sizing agent had low heat resistance and weak interface performance.
[0098] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A carbon fiber sizing agent, characterized in that: It includes benzoxazine resin, amino modified resin, emulsifier and solvent.
2. The carbon fiber sizing agent according to claim 1, characterized in that In parts by weight, it includes: 100 parts of benzoxazine resin, 20-50 parts of amino modified resin, 20-40 parts of solvent and 30-50 parts of emulsifier.
3. The carbon fiber sizing agent according to claim 1, characterized in that: The particle size of the carbon fiber sizing agent is 200-500nm.
4. The carbon fiber sizing agent according to any one of claims 1 to 3, characterized in that The benzoxazine resin includes one or more of bisphenol A-type benzoxazine, bisphenol F-type benzoxazine and phenol-type benzoxazine.
5. The carbon fiber sizing agent according to any one of claims 1 to 3, characterized in that: The amino-modified resin includes one or more of urea-formaldehyde resin, melamine-formaldehyde resin and benzoguanamine-formaldehyde resin.
6. The carbon fiber sizing agent according to any one of claims 1 to 3, characterized in that The solvent includes one or more of toluene, acetone and tetrahydrofuran.
7. The carbon fiber sizing agent according to any one of claims 1 to 3, characterized in that The emulsifier includes one or more of alkylphenol polyoxyethylene ether, polyethylene glycol and polyoxyethylene sorbitan fatty acid ester.
8. A method for preparing a carbon fiber sizing agent according to any one of claims 1 to 7, characterized in that: include: The benzoxazine resin, the amino-modified resin, the emulsifier and the solvent are stirred and mixed, and water is added for emulsification and phase inversion to obtain the carbon fiber sizing agent.
9. A sized carbon fiber, characterized in that: Comprising carbon fibers and a sizing agent coating attached to the surface of the carbon fibers, wherein the sizing agent coating is formed by the carbon fiber sizing agent according to any one of claims 17; Optionally, the mass fraction of the sizing agent coating on the carbon fiber is 0.5-1.0%.
10. A method for preparing sized carbon fiber according to claim 9, characterized in that: include: The sizing agent is prepared into a sizing agent solution, the carbon fiber is immersed in the sizing agent solution, and then the treated carbon fiber is dried and heated and cured in sequence to obtain the sized carbon fiber; Optionally, the drying conditions include: drying temperature of 130-160° C., drying time of 30-60 s; Optionally, the heating and curing conditions include: a heating temperature of 180-220° C. and a heating time of 30-60 s.
Citation Information
Patent Citations
Carbon fiber
CN103069063A
High-temperature-resistant emulsion type sizing agent as well as preparation method and application thereof
CN118531636A
Prepreg for composite material and composite material
JP2007016121A
Intermediate for composite material molding and fiber−reinforced composite material
WO2003018674A1
Cited By
Low-temperature-resistant anti-seepage carbon fiber reinforced composite material and preparation method thereof
CN121374903A